OS 08-05 NOVEL MOLECULAR INSIGHTS IN URINARY EXOSOME PROTEIN PROFILING IN THIAZIDE INDUCED HYPONATREMIA. (September 2016) - Channavajjhala, Sarath; Jia, Wenjing; Jalland, Mahli; O'Shaughnessy, Kevin; Hall, Ian; Glover, Mark
Abstract : Objective: Thiazide diuretics are amongst most widely prescribed and effective anti-hypertensive medicines worldwide. Thiazides however cause Thiazide-Induced Hyponatremia (TIH), a novel and potentially important paradigm of dysregulated distal nephron sodium and water reabsorption. A priori TIH must result from excessive saliuresis and/or water reabsorption. The water and electrolyte transporter composition of Urinary Exosomes (UE) reflects their cellular origin and are a promising way to study renal dysfunction. This study assessed the expression of aquaporin 2 (AQP2), thiazide - sensitive sodium chloride co-transporter (NCC) and Phospho NCC (PNCC) in the UE of TIH patients. Advancements in understanding of thiazide-sensitive pathways may further uncover the molecular mechanisms underlying sodium and water trafficking. Design and Method: 100 patients with severe TIH donated urine samples during acute TIH and at two months post thiazide cessation. Matched normonatraemic controls were recruited both on and off thiazides (groups 1 & 2 respectively). UE from each patient group were isolated and AQP2, NCC and PNCC were evaluated by immunoblotting. Protein expression was normalized by urinary creatinine (UCr) and results expressed as units of optical density/UCr. Results: UE expression of AQP2 was higher in acute TIH compared to convalescent (32.93 vs 28.71, P < 0.01) and control groups 1 & 2 (15.61 and 15.09 respectively, P < 0.001). NCC expression was lower in acute TIH patients compared to convalescent (17.72 vs 31.86, P < 0.05) and control groups 1 & 2 (30.32 and 31.17, P < 0.05). PNCC expression however was higher in acute TIH patients compared to convalescent and both control groups. Conclusions: This study highlights the utility of UE analysis to probe the molecular pathophysiology of TIH. Increased AQP2 and reduced NCC expression suggests that TIH results from increased water reabsorption and sodium wasting in the distal nephron. TIH studies may further inform the design of new thiazide medicines less prone to cause hyponatremia.